(untitled) (Journal of Laboratory Animal Science, 2024)
Bovine mastitis in an economically important disease of dairy cattle and caused by multi etiological factors. In the present study, milk viable bacterial count in mouse mastitis induced by Staphylococcus epidermidis, S. chromogenes, S. haemolyticus and S. aureusisolated from apparently normal bovine milk was studied. The 2 x 104CFUorganisms in 50 µl per teat were inoculated through intramammary route in 4th and 5th pairs of abdominal mammary gland in mice. The mouse milk ranging from 50 to 200 µl per mice wascollectedat 6, 12, 24, 48, 72 and 96 hrs after intramammary inoculation. The milk was diluted with sterile PBS and subjected to bacterial countby pour plate method. The viable bacterial count in mice milk showed significant (P<0.05) increase in bacterial colonies at 12, 24, 48 and 72hrs after S. aureus infection in mice. The three coagulase negative staphylococci(CNS) species showed initial increase in bacterial counts at 12 and 24 hrs but declined from 48 to 96 hrs after IMI in mice. Thus, CNS species can increase the mice viable bacterial count moderately but ten to fifteen fold increase was observed in S. aureus infected mice mammary gland.This indicated the subclinical nature of CNS intramammaryinfection in mice and also the host ability to overcome and eliminate the CNS infection. Mouse is a suitable model to study coagulase negative staphylococcus species induced bovine subclinical mastitis.